2016
DOI: 10.1590/s0100-83582016340400011
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Architectural Traits that Allow the Regeneration of Eustachys retusa (poaceae) in Systems with Intensive Glyphosate Application

Abstract: -Eustachys retusa has low sensitivity to glyphosate at the reproductive stage. The purpose of this study was to analyze the effect of glyphosate on adult E. retusa plants in order to identify the traits that make possible their regeneration in no-tillage systems. For this purpose, reproductive-stage specimens from wild populations were treated with glyphosate at two different rates (480 and 1,200 g a.i. ha dose. However, a certain proportion of plants can survive despite having full chlorosis as a consequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…For this purpose, the nodes per axes were divided into three groups based on their position along the principal axis. These groups or zones were designated as apical, mid, and basal according to previous studies (Panigo et al, 2012(Panigo et al, , 2016.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For this purpose, the nodes per axes were divided into three groups based on their position along the principal axis. These groups or zones were designated as apical, mid, and basal according to previous studies (Panigo et al, 2012(Panigo et al, , 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Kunth (Argentine fingergrass) are plant species native to South America and frequently reported as species with low sensitivity to glyphosate (Puricelli & Faccini, 2005;Dellaferrera et al, 2007;Nisensohn et al, 2011;Panigo et al, 2012Panigo et al, , 2016. In previous morphological studies, we found that both species survive after glyphosate applications thanks to their ability to recover foliar mass through the regrowth of buds that are not developed under normal conditions (Panigo et al, 2012(Panigo et al, , 2016. Therefore, the application of glyphosate to C. erecta and E. retusa would not affect their bud bank and consequently their ability to resprout.…”
Section: Commelina Erecta L (Dayflower) Andmentioning
confidence: 99%
See 3 more Smart Citations